Analisa Efektivitas Pajak Bumi dan Bangunan untuk Meningkatkan Pendapatan Asli Daerah di Kabupaten Nganjuk Tahun 2014 -2018 - Supraptianik Supraptianik; Dwi Puji Rahayu; Ambarwati Ambarwati; Devi Kusumawardani (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2022)
The purpose of this study is : (1) to find out the effectiveness of land and building tax to increase local revenue in Nganjuk district. (2) to find out the supporting factors in land and building taxes on the increase in local original income in Nganjuk Regency. (3)to find out the inhibiting factors in of land and building tax on the increase of local original income in Nganjuk Regency. This research is primary and secondary research with qualitative methods. This study is the result of an analysis of the effectiveness of the report on the realization of the land and building tax regarding the increase in local revenue from the Nganjuk Regional Revenue Agency. The size of the data taken by researchers that is for four years from 2014 to 2018 is calculated by the effectiveness method according to Abdul Halim (2008:234) if what is achieved is at least one year 100%, the ratio of effectiviness is getting better,meaning that the more effective the land and building tax. The result of the study showed that the level of effectiveness of the Nganjuk district land and building tax as a whole as seen from the average each year was effective. The highest effecteness occurred in 2018 amounting to 1044,46% while the lowest in 2015 was 34,23%.